Radial and local time structure of the Saturnian ring current, revealed by Cassini. Issue 2 (15th February 2017) - Sergis, N.; Jackman, C. M.; Thomsen, M. F.; Krimigis, S. M.; Mitchell, D. G.; Hamilton, D. C.; Dougherty, M. K.; Krupp, N.; Wilson, R. J.
Abstract: We analyze particle and magnetic field data obtained between July 2004 and December 2013 in the equatorial magnetosphere of Saturn, by the Cassini spacecraft. The radial and local time distribution of the total (thermal and suprathermal) particle pressure and total plasma beta (ratio of particle to magnetic pressure) over radial distances from 5 to 16 Saturn radii ( RS = 60, 258 km) is presented. The average azimuthal current density J ϕ and its separate components (inertial, pressure gradient, and anisotropy) are computed as a function of radial distance and local time and presented as equatorial maps. We explore the relative contribution of different physical mechanisms that drive the ring current at Saturn. Results show that (a) the particle pressure is controlled by thermal plasma inside of 8 RS and by the hot ions beyond 12 RS, exhibiting strong local time asymmetry with higher pressures measured at the dusk and night sectors; (b) the plasma beta increases with radial distance and remains >1 beyond 8–10 RS for all local times; (c) the ring current is asymmetric in local time and forms a maximum region between 7 and 13 RS, with values up to 100–115 pA/m 2 ; and (d) the ring current is inertial everywhere inside of 7 RS, exhibits a mixed nature between 7 and 11 RS and is pressure gradient driven beyond 11 RS, with the exception of the noon sector where the mixed nature persists. In the dawn sector, it appears strongly pressure gradient driven for a wider range of radial distance, consistent with fast return flow of hot, tenuous magnetospheric plasma following tail reconnection. Key Points: The global properties and nature of the Saturnian ring current are revealed after 10 years of Cassini magnetic field and plasma measurements The Saturnian ring current is inertial inside of 7 RS, pressure gradient driven beyond 12 RS, and mixed in nature between 7 and 11 RS The maximum azimuthal current flows in dusk and night, between 7 and 11 RS, reaching 100‐120 pA/m 2 ; plasma beta becomes greater than 1 beyond 8‐10 RS